Effect of interfacial transition zone on the transport of sulfate ions in concrete. (20th December 2018) - Sun, Dandan; Wu, Kai; Shi, Huisheng; Zhang, Lintao; Zhang, Lihai
Highlights: Reactive transport model of sulfate ions in concrete were proposed. The effect of interfacial transition zone (ITZ) on the transport of sulfate ions was researched. Experiments to obtain the content of sulfate ions and porosity of ITZ were carried out. The distribution of ettringite in ITZ and concrete were simulated. Abstract: Long-term external sulfate attack can result in significant concrete degradation. The purpose of this study is to develop an experimentally validated reactive transport model to investigate the transport behaviour of sulfate ions in concrete containing interfacial transition zone (ITZ). The model takes into account the spatially dependent pore size in ITZ and the change of diffusion coefficient of sulfate ions due to the formation of ettringite and gypsum in concrete pores resulting from the chemical reaction between sulfate ions and concrete components. The developed model was firstly validated by performing a series of experiments involving concrete specimens and sodium sulfate solution. Then, a series of parametric studies were carried out to identify the critical parameters that govern the transport of sulfate ions in concrete. The backscattered electron microscopy (BSE) results show that the porosity of concrete within ITZ is relatively higher than that in bulk paste with a six-fold higher porosity in inner ITZ (5 µm from aggregate surface) than that in outer ITZ (50 µm from aggregate surface). The model predictions suggested that the concentration of sulfate ions initially increases rapidly in concrete during the first 20 days and then the rate of increase gradually decreases due to the reduction in the diffusion coefficient of ions as a result of the ettringite and gypsum formation in concrete pores. In addition, it demonstrates that self-induced electric field has little influence in the transport of sulfate ions.